“I think I can”: achievement-oriented themes in storybooks from Indonesia, Japan, and the United States - Suprawati, Maria; Anggoro, Florencia K.; Bukatko, Danuta (Frontiers in Psychology, 2014)
The focus of the present study is on the ways in which storybooks communicate cultural ideals about achievement orientation, and in particular, the role of effort, perseverance, and hard work in fostering successful outcomes. Sixty preschool children’s books from Indonesia, Japan, and the United States (20 from each country) were examined for the presence of achievement-oriented themes. These countries were chosen due to previously documented cultural differences in models of learning and individualist/collectivist tendencies that could have some bearing on achievement outcomes. Texts were assessed for (1) the frequency with which “challenge events” appeared in the narratives, (2) whether these events derived from sources internal or external to the main character, and (3) whether solutions relied on the main character individually or included the assistance of others. Results show that Japanese storybooks contained significantly more challenge events than Indonesian storybooks. Compared with Japanese storybooks, American storybooks tended to include a greater proportion of challenges derived from internal qualities of the main character as opposed to external factors. Compared with American storybooks, Japanese storybooks contained a significantly greater proportion of challenges that were solved with individual efforts as opposed to efforts involving the assistance of others. Findings from this study contribute to our understanding of how storybook contexts can provide a rich source of information for young children learning about culturally valued qualities and behaviors related to achievement.